A geografia econômica da indústria de embalagens plásticas: inovação tecnológica e dinâmica espacial - Limberger, Silvia Cristina (2010)
This study is a review of capital accumulation in plastic packaging industry in Brazil, specifically targeted to the State of Parana, where we seek to discover how the industry has developed in this sector especially in the state and its regions with slow industrial development, where characterizes the consolidation of traditional sectors with lower technological level. To understand the dynamics of the packaging sector, there are some key elements as, II PND Policy (National Development Plan), which required investment for all Brazilian petrochemical chain in the 1970s; expansion of the national petrochemical industry and its reorganizing production in the 1990s; goods manufacturing industry for the plastic packaging sector that constitutes a lever for development; food and beverage industry, the main consumer market of plastic packaging. We demonstrate these features from the case study and analysis of spatial strategies of companies linked to the sector in the state of Parana.